Phylogenetic position of a remarkable new fideliine bee from northern Chile (Hymenoptera: Megachilidae). (July 2017) - PACKER, LAURENCE; LITMAN, JESSICA; PRAZ, CHRISTOPHE J.
Abstract: Fideliine bees are an archaic group with a disjunct distribution mostly restricted to deserts of South America and South Africa. This group was previously thought to be more diverse in Africa than in South America, where only one genus ( Neofidelia ) comprising five species is known. Here we describe a species belonging to a second South American genus: Xenofidelia colorada Packergen. et sp.n., from northern Chile. The species is illustrated and its phylogenetic position within Megachilidae is assessed using morphological, molecular and combined data. The 214 character morphological matrix includes 55 new characters with an additional 16 hitherto unexplored for megachilid phylogeny. The molecular dataset is based upon seven nuclear gene sequences, totalling 6439 bp, many of which are published for the first time for particular megachilid taxa. In all analyses, Xenofidelia was found as sister to Neofidelia (endemic to Chile and Peru). It differs from that genus most notably in its short mouthparts, absence of a glossal rod, unmodified female metabasitarsus and an elongate and horizontal dorsal surface of the metapostnotum. Morphological and combined data support a monophyletic Fideliinae (excluding Pararhophites ), while molecular data alone failed to recover fideliine monophyly. Dating analyses suggest that Xenofidelia and Neofidelia diverged 34.3–40.6 Ma, indicating that New World fideliines were probably present in arid habitats of South America during the Eocene. This divergence time predates both the main orogenic events that resulted in the formation of the Andean mountains and the origin of hyperarid conditions in the Atacama Desert; it also corresponds to a period prior to the origin of the summer rainfall area in the far north of Chile where the new genus is found. These results support the view that arid habitats have been present continuously in South America since the Eocene. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:EA69BB4A‐6F59‐4A15‐AB44‐2A8949E3CF8F .